2022
DOI: 10.3389/fcimb.2022.940937
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity and the impact of associated early-life inflammation on long-term health of offspring

Abstract: The prevalence of obesity is increasingly common in the United States, with ~25% of women of reproductive age being overweight or obese. Metaflammation, a chronic low grade inflammatory state caused by altered metabolism, is often present in pregnancies complicated by obesity. As a result, the fetuses of mothers who are obese are exposed to an in-utero environment that has altered nutrients and cytokines. Notably, both human and preclinical studies have shown that children born to mothers with obesity have hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 241 publications
0
20
0
1
Order By: Relevance
“…Existe evidencia que señala que los riesgos de la cesárea son mayores y más complejos en las embarazadas obesas. Aparte de presentar mayores probabilidades de indicación de interrupción del embarazo por vía abdominal, también tienen mayor riesgo de complicaciones postoperatorias asociadas a la obesidad (por ejemplo, preeclampsia) (21)(22)(23) . Aunque la cesárea es un buen indicador de los posibles efectos de la obesidad sobre las alteraciones del parto, la información que puede suministrar debe ser analizada cuidadosamente, ya que puede ser afectada por múltiples factores.…”
Section: Discussionunclassified
“…Existe evidencia que señala que los riesgos de la cesárea son mayores y más complejos en las embarazadas obesas. Aparte de presentar mayores probabilidades de indicación de interrupción del embarazo por vía abdominal, también tienen mayor riesgo de complicaciones postoperatorias asociadas a la obesidad (por ejemplo, preeclampsia) (21)(22)(23) . Aunque la cesárea es un buen indicador de los posibles efectos de la obesidad sobre las alteraciones del parto, la información que puede suministrar debe ser analizada cuidadosamente, ya que puede ser afectada por múltiples factores.…”
Section: Discussionunclassified
“…There is concern that an altered inflammatory state can impact the growing fetus indirectly by altering a variety of placental functions (e.g., trophoblast invasion or nutrient transport) 98 . Aye et al found that increased maternal BMI was associated with activation of placental p38-MAPK and STAT signaling, demonstrating that inflammation associated with maternal obesity is regulated by altered placental function 99 .…”
Section: Inflammation In Female Reproduction With Obesitymentioning
confidence: 99%
“…It is increasingly acknowledged as an early‐life factor that influences offspring health 3 . Mothers with pre‐pregnancy obesity tend to have high circulating levels of pro‐inflammatory markers/cytokines, such as IL‐8, IL‐6, CRP, TNF‐α, IFN‐γ, and altered adipokine level 4 . Human data have revealed that the activated pro‐inflammatory state during pregnancy is linked to adverse health outcomes in offspring, including childhood obesity 4 .…”
Section: Introductionmentioning
confidence: 99%
“… 3 Mothers with pre‐pregnancy obesity tend to have high circulating levels of pro‐inflammatory markers/cytokines, such as IL‐8, IL‐6, CRP, TNF‐α, IFN‐γ, and altered adipokine level. 4 Human data have revealed that the activated pro‐inflammatory state during pregnancy is linked to adverse health outcomes in offspring, including childhood obesity. 4 Animal experiments have demonstrated that fetal inflammation induced by maternal obesity significantly contributes to the promoting adipogenesis and increasing adiposity in the offspring.…”
Section: Introductionmentioning
confidence: 99%